Antipsycothic drugs in dementia and Alzheimer's disease: pharmacovigilance plan in Florence. Issue 2 (12th March 2012) - Pazzagli, L.; Benedetti, E.; Agostino, E.; Romano, F.; De Angelis, A.; Romagnoli, F.; Tucci, R.; Bazzechi, A.; Brocca, T.; Piccininni, M.
Abstract : Background: The Italian Medicine Agency (AIFA) with a specific directive (Dir. AIFA 28/12/2006) requires the monitoring of off-label prescriptions of the antipsychotic drugs in patients with dementia, used to control personality disorder and agitation symptoms. Purpose: The aim of this study was to define an informed consent by patients with dementia, who are not able to consciously choose, and to monitor adverse drug reactions (ADRs). Materials and methods: Medical record included prescription and treatment follow-up. Pharmaceutical data included prescribed drugs and adverse events. Data record included patient's demographic characteristics. Results: The cooperation between medical team (Neurologists and Geriatricians of Florence) and Pharmacovigilance Centre, has generated an information paper for caregivers and /or patient's family (to explain drug side effects and the reason for seeking consent), an informed consent and a monitoring plan for each patient. Data analysis, lasted from January 2007 to December 2010, were performed every 6 months from Pharmacovigilance Centre. Treated patients were 1632 (622 men and 1010 women), aged from 50 to 103 years (average 76 years ) . The most prescribed drugs were olanzapine (45.7%) quetiapine (38.7%) and risperidone (7.9%). Identified adverse reactions were 7.9% (129 ADRs of 1632 patients), mainly not serious type and primarily dependent on olanzapine (7.69%) and quetiapine (5.87%). Frequent reactions were: extrapyramidal syndrome, joint stiffness, excessive sedation, akathisia, dyskinesia, confusion and ineffectiveness. Conclusions: Informed consent and information on the risks of antipsychotic adverse reactions are important goals to improve patient safety, especially for those with dementia and Alzheimer's disease. This study is an innovative example in Italy for critical issues resolution because it leads to an integrated therapeutic and diagnostic path.